Analysis of CD83 antigen expression in human breast fibroadenoma and adjacent tissue - Borges, Marcus Nascimento; Facina, Gil; Silva, Ismael Dale Cotrin Guerreiro; Waitzberg, Angela Flávia Logullo; Nazario, Afonso Celso Pinto (São Paulo Medical Journal, 2011)
CONTEXT AND OBJECTIVE: Dendritic cell maturation is considered essential for starting an immune response. The CD83 antigen is an important marker of dendritic cell maturation. The objectives here were to analyze CD83 antigen expression in human breast fibroadenoma and breast tissue adjacent to the lesion and to identify clinical factors that might influence this expression. DESIGN AND SETTING: This was a retrospective study at a public university hospital, in which 29 histopathological samples of breast fibroadenoma and adjacent breast tissue, from 28 women of reproductive age, were analyzed. METHODS: The immunohistochemistry method was used to analyze the cell expression of the antigen. The antigen expression in the cells was evaluated by means of random manual counting using an optical microscope. RESULTS: Positive expression of the CD83 antigen in the epithelial cells of the fibroadenoma (365.52; standard deviation ± 133.13) in relation to the adjacent breast tissue cells (189.59; standard deviation ± 140.75) was statistically larger (P < 0.001). Several clinical features were analyzed, but only parity was shown to influence CD83 antigen expression in the adjacent breast tissue, such that positive expression was more evident in nulliparous women (P = 0.042). CONCLUSIONS: The expression of the CD83 antigen in the fibroadenoma was positive and greater than in the adjacent breast tissue. Positive expression of the antigen in the adjacent breast tissue was influenced by parity, and was significantly more evident in nulliparous women.